Extraterritorial Act versus the Indigenous People Protection: An Analysis of the European Union Deforestation-Free Regulation - Tehupeiory, Aartje; Simbolon, Putu George Matthew (Faculty of Law, Universitas Padjadjaran, 2024)
At first glance, indigenous people and international trade appear to be two separate issues. However, this perception does not apply in the case of European Regulation 2023/1115. This study aims to provide an understanding of how Indonesia should respond to the EU DFR, which has affected Indonesia’s national interests in protecting indigenous people. This study applied a normative method through doctrinal and conceptual approaches to achieve the objective. The study covers two main discussions. The first explains how due diligence under the EU DFR has indirectly pushed Indonesia to become an EU trading partner and provide more excellent protection for local indigenous people to gain access to the Union’s market for its agricultural products. The second discussion explains how Indonesia should respond to this regulation by considering protecting its indigenous people and ensuring the availability of market access for Indonesian companies and traders. The first discussion states that the EU DFR will prohibit the export and import of agricultural products if the trading partner’s company does not provide adequate legal protection for its indigenous people. The second discussion suggests that Indonesia must better protect its indigenous people to secure market access to the European Union. However, if the EU regulator acts arbitrarily, Indonesia reserves the right to address these issues through the available means of trade dispute settlement under international law.